2002
DOI: 10.1074/jbc.m203813200
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Activates Cardiac Fatty Acid Oxidation Independent of Changes in the AMP-activated Protein Kinase-Acetyl-CoA Carboxylase-Malonyl-CoA Axis

Abstract: Leptin regulates fatty acid metabolism in liver, skeletal muscle, and pancreas by partitioning fatty acids into oxidation rather than triacylglycerol (TG) storage. Although leptin receptors are present in the heart, it is not known whether leptin also regulates cardiac fatty acid metabolism. To determine whether leptin directly regulates cardiac fatty acid metabolism, isolated working rat hearts were perfused with 0.8 mM [9,10-3 H]palmitate and 5 mM [1-14 C]glucose to measure palmitate and glucose oxidation ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
120
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(130 citation statements)
references
References 47 publications
8
120
1
1
Order By: Relevance
“…These previous studies demonstrated that increased MV O 2 , MFAUp, and MFAO were associated with decreased efficiency. [27][28][29] The results of the present study show that obese humans, who have alterations in MV O 2 and myocardial fatty acid metabolism, also have changes in the translation of energy to contractile function.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…These previous studies demonstrated that increased MV O 2 , MFAUp, and MFAO were associated with decreased efficiency. [27][28][29] The results of the present study show that obese humans, who have alterations in MV O 2 and myocardial fatty acid metabolism, also have changes in the translation of energy to contractile function.…”
Section: Discussionsupporting
confidence: 51%
“…The young, obese women in the present study displayed evidence of insulin resistance, on the basis of plasma glucose AUC during an oral glucose tolerance test, that was presumably responsible for increased MFAUp, MFAU, and MFAO, although increased levels of adipokines, such as leptin, may also be partly responsible for the increased myocardial fatty acid metabolism in obesity. 29,30 In addition, hyperinsulinemia, which stimulates insulin-like growth factor-1 (IGF-1) receptors, is also likely involved in the pathogenesis of myocardial hypertrophy observed in obese women in the present study. 31 However, obese subjects in the present study did not yet manifest clinical or echocardiographic evidence of contractile dysfunction, which suggests that more prolonged alterations in substrate metabolism and increased myocardial mitochondrial oxidative stress are needed to decrease LV contractility.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Leptin may also have effects on the AMPK system. It has been shown that leptin directly and indirectly activates AMPK in skeletal muscle (7) and white adipocytes (44), although not in heart (45). The effects of leptin on AMPK in liver are not fully known.…”
Section: Discussionmentioning
confidence: 99%
“…6 One recent report indicates that leptin can also stimulate fatty acid oxidation independent of changes in AMPK activity. 7 In addition to these direct effects on fatty acid metabolism, leptin also activates sympathetic nervous system activity 2 leading to adipocyte lipolysis and increased systemic fatty acid oxidation. 2 Thus, serum leptin can activate systemic fatty acid oxidation both directly at the level of intermediary metabolism and indirectly via modulation of sympathetic tone.…”
mentioning
confidence: 99%